ANALISIS INTEGRASI METODE SARISWARA PADA MATA KULIAH KARAWITAN - Dani Setyawan, Arya; Trisharsiwi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
Education in Indonesia in the era of the Covid-19 pandemic has experienced significant dynamics. Starting from learning strategies with systems in the network (online) to implementing the education system in a new way. Technology is developing very rapidly today, even humans can do anything with the technology. This is an advantage as well as a weakness that must be understood together in the world of education. The output of education is not only to make students smart but also to build mental, spiritual, and high integrity. For this reason, it is needed not only the ability to use technology but also to hone reason and mind so that they can have good character. Tamansiswa in this case still inherits the teachings of Ki Hadjar Dewantara which in its implementation is very useful for online learning needs. The Among system approach in the implementation of learning is expected to be an effective strategy for the implementation of the lesson in karawitan courses. This study uses a descriptive qualitative research approach so that researchers can describe and answer the problems of a phenomenon or current event. Regarding the implementation of learning with the online system, the researcher used a sample of Ki Hadjar Dewantara's teachings, namely the Among system and the Sariswara method in single variables as well as correlations and or comparisons of various variables. It can be understood that the descriptive research method is a method used to describe the situation in the field, supported by facts obtained employing observation and in-depth research to seek understanding and correctness of the data.